Deciphering immune responses primed by a bacterial lipopeptide in wheat towards Zymoseptoria tritici - Platel, Rémi; Lucau-Danila, Anca; Baltenweck, Raymonde; Maia-Grondard, Alessandra; Trapet, Pauline; Magnin-Robert, Maryline; Randoux, Béatrice; Duret, Morgane; Halama, Patrice; Hilbert, Jean-Louis; Coutte, François; Jacques, Philippe; et al. (Frontiers in Plant Science, 2023)
Plant immunity induction with natural biocontrol compounds is a valuable and promising ecofriendly tool that fits with sustainable agriculture and healthy food. Despite the agroeconomic significance of wheat, the mechanisms underlying its induced defense responses remain obscure. We reveal here, using combined transcriptomic, metabolomic and cytologic approach, that the lipopeptide mycosubtilin from the beneficial bacterium Bacillus subtilis, protects wheat against Zymoseptoria tritici through a dual mode of action (direct and indirect) and that the indirect one relies mainly on the priming rather than on the elicitation of plant defense-related mechanisms. Indeed, the molecule primes the expression of 80 genes associated with sixteen functional groups during the early stages of infection, as well as the accumulation of several flavonoids during the period preceding the fungal switch to the necrotrophic phase. Moreover, genes involved in abscisic acid (ABA) biosynthesis and ABA-associated signaling pathways are regulated, suggesting a role of this phytohormone in the indirect activity of mycosubtilin. The priming-based bioactivity of mycosubtilin against a biotic stress could result from an interaction of the molecule with leaf cell plasma membranes that may mimic an abiotic stress stimulus in wheat leaves. This study provides new insights into induced immunity in wheat and opens new perspectives for the use of mycosubtilin as a biocontrol compound against Z. tritici.